Molecular evolution of TRPC4 regulatory sequences supports a role in mammalian thermoregulatory adaptation - Cornman,Robert S. (PeerJ, 2025)
Background Proteins encoded by the canonical transient receptor potential (Trpc) gene family form transmembrane channels involved in diverse signal-transduction pathways. Trpc4 has been shown necessary for the induction of nonshivering thermogenesis (NST) in mice, a key component of which is thermogenic brown adipose tissue (BAT). In bats, Trpc4 exhibited diversifying selection within exons encoding regulatory binding sites of TRPC4. Methods To assess whether diversification of these regulatory sequences mirrors the diversification of mammalian thermoregulatory strategies, the ratio of nonsynonymous to synonymous substitutions (ω) was estimated for multiple tetrapod outgroups and eutherian orders. Four questions were addressed: (1) Did the ancestral eutherian Trpc4 diverge under positive selection from nonplacental mammals that lack BAT? (2) Did Trpc4 subsequently become more constrained in descendant eutherian clades? (3) In eutherian clades that subsequently lost BAT by inactivation of the thermogenin gene Ucp1, did Trpc4 become less constrained? (4) Does the evolutionary rate of Trpc4 differ between quantitatively more heterothermic mammal orders (bats and rodents) relative to quantitatively less heterothermic outgroups (carnivores, artiodactylids, and primates)? Results Coincident with the advent of BAT, Trpc4 evolutionary rate increased significantly in ancestral eutheria after their divergence from nonplacental mammals but a branch-site model did not support a rate class ω > 1 along that branch. In descendant eutherian mammals, Trpc4 became far more constrained, with an evolutionary rate less than half that of tetrapod clades lacking NST, a pattern was not seen in other Trp channel genes. Intensifying selection in descendent eutherian mammals was further supported with the RELAX program, which also indicated reduced constraint on Trpc4 in clades that have secondarily lost BAT. However, no consistent pattern was identified within mammalian orders with strong variation in heterothermy: evidence of increased evolutionary rate was again found in bats for Trpc4 as well as homologs it directly binds in heteromeric membrane channels (Trpc5 and Trpc1), yet all rodent Trpc genes had low evolutionary rates. Evolutionary rates of Trpc4 and Trpc1 in bats were consistent with relaxed constraint whereas bat Trpc5 experienced diversifying selection. Most variation among tetrapod TRPC4 sequences lies within an  85 amino-acid window that is functionally uncharacterized. Sequence alignments demonstrated that the TRPC4 β isoform, which lacks a portion of the C-terminal regulatory region, originated in basal eutherians but appears to be lost in many tip lineages. Collectively, the data indicate that the C-terminal region of TRPC4 has responded to selection on NST thermoregulation during the diversification of eutherian mammals. The drivers of increased diversification of Trpc4 and interacting genes in bats remain to be determined.
Keywords: Adaptation; Molecular evolution; Positive selection; Evolutionary rates; Mammals; Thermoregulation; Transient receptor potential channels; Nonshivering thermogenesis; Brown adipose tissue